Research on AHP-based fuzzy evaluation of the spatial environment recovery of community parks in cold cities - Zhang Hongbo; Liang Yaru (E3S Web of Conferences, 2023)
Community parks provide many spatial environments and healing places in cold regional cities, and are important for human well-being, satisfaction and mood regulation. However, few studies have comprehensively explored the effects of weak support for health and recovery in cold cities. The new method integrated fuzzy mathematical evaluation into an analytical hierarchical process (AHP) approach to analyze the relationship between health restoration influence mechanisms and environmental elements, proposed four evaluation factors, including the restorability of the natural landscape, of psychological perception, of spatial facilities and of the surrounding environment, and constructed the basic framework of a spatial environmental restorability evaluation system in cold regions. Therefore, taking Harbin’s Shangzhi Park as an example, this study uses AHP to construct an evaluation system for the spatial environmental recovery of community parks in cold cities. The research finds that natural landscape restorability is more important than other environmental factors, and plant species richness is important for healing physical and mental health.